Deep Brain Stimulation: Emerging Tools for Simulation, Data Analysis, and Visualization - Wårdell, Karin; Nordin, Teresa; Vogel, Dorian; Zsigmond, Peter; Westin, Carl-Fredrik; Hariz, Marwan; Hemm, Simone (Frontiers in Neuroscience, 2022)
Deep brain stimulation (DBS) is a well-established neurosurgical procedure for movement disorders and is also being explored for treatment-resistant psychiatric conditions. This review highlights important consideration for DBS simulation and data analysis. The literature on DBS has expanded considerably in recent years, and this article aims to identify important trends in the field. During DBS planning, surgery, and follow up sessions, several large data sets are created for each patient, and it becomes clear that any group analysis of such data is a big data analysis problem and has to be handled with care. The aim of this review is to provide an update and overview from a neuroengineering perspective of the current DBS techniques, technical aids, and emerging tools with the focus on patient-specific electric field (EF) simulations, group analysis and visualization in the DBS domain. Examples are given from the state of the art literature including our own research. This work reviews different analysis methods for EF simulations, tractography, deep brain anatomical templates and group analysis. Our analysis highlights that group analysis in DBS is a complex multi-level problem and selected parameters will highly influence the result. DBS analysis can only provide clinically relevant information, if the EF simulations, tractography results, and derived brain atlases are based on as much patient-specific data as possible. A trend in DBS research is creation of more advanced and intuitive visualization of the complex analysis results suitable for the clinical environment.